The concurrent variability of East Asian subtropical and polar‐front jets and its implication for the winter climate anomaly in China - Xiao, Chuliang; Zhang, Yaocun; Lofgren, Brent M.; Nie, Yu (Journal of Geophysical Research: Atmospheres, 2016)
The variability of East Asian upper level westerly jets in winter is studied with regard to the concurrent existence of subtropical jet (East Asian subtropical jet (EASJ)) and polar‐front jet (East Asian polar‐front jet (EAPJ)) using the National Centers for Environmental Prediction/National Center for Atmospheric Research reanalysis. In the distribution of jet occurrence revealed in 6‐hourly data, two jet branches along 30°N and 55°N, corresponding to locations of EASJ and EAPJ, respectively, are separated over the Tibetan Plateau. The leading two modes of zonal‐mean zonal wind in East Asia extracted from a mass‐weighted empirical orthogonal function analysis are characterized by the intensity changes and location displacements of two jets. The key regions for EASJ and EAPJ are then defined to represent variabilities of these two jets. Correlation analysis indicates that the subseasonal variation of EAPJ precedes EASJ by around 5 days, which can be interpreted as wave‐mean flow interactions via synoptic‐scale transient eddy activities. Based on the pentad intensity indices of two jets, the concurrent variabilities of EASJ and EAPJ are investigated with typical temperature and precipitation anomalies in China. The results suggest that by taking account of the two jets, we are able to get a more comprehensive understanding of the winter climate.Key PointsThe leading modes of zonal‐mean zonal wind in East Asia and the concurrent existence of East Asian subtropical jet and polar‐front jetTheir concurrent variability can be interpreted as wave‐mean flow interactions via synoptic‐scale transient eddy activitiesA comprehensive understanding of the winter climate in China from the perspective of double jets Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/133534/1/jgrd53070_am.pdf http://deepblue.lib.umich.edu/bitstream/2027.42/133534/2/jgrd53070.pdf